Household debt and financial wellbeing in Pakistan / Wajiha Haq - Wajiha, Haq (2018)
With changing economic situations, problem of household debt is becoming one of the main highlights. However, in the developing world, there are some countries where efforts of increasing financial inclusion through debt provision are being made. About one-third of the population in Pakistan does not borrow. Around 80 per cent of the non-borrowing population does not even plan to borrow in next two to three years (Nenova et al., 2009). Although efforts to increase the outreach of financial services have been made but credit products do not really excite people to take debt. Debt is one of the financial resources that can be used for financial management as well as to increase financial wellbeing if the financial management remains wise (Lown & Ju, 1992). Understanding socioeconomic and demographic factors influencing debt is very important to guide policy design. Debt is not important unless it helps to increase financial wellbeing. The aim of the research is to investigate the characteristics of people (household heads) which affect their debt decision and the amount of household debt. This research also investigates the effect of debt on the financial wellbeing along with other demographic and socioeconomic characteristics. This research also models the random variations in household debt decision, household demand and financial wellbeing at provincial level using multilevel analysis. The Household Integrated Expenditure Survey (HIES) data from 2001-2014 which includes six survey rounds. The study revealed that the likelihood of taking debt was influenced by employment status, residential region, age, education, financial assets and household sizes. It was also seen that the decision of taking household debt randomly varies at provincial level. After knowing the characteristics affecting the decision to take debt, it is important to know the characteristics affecting size of participation in order to understand that whether same characteristics affect both. People having higher financial assets, higher income and larger household sizes have higher amount of debt. The amount of debt also increases with education and age. This study also investigates the role of debt in financial wellbeing. It aims to investigate financial wellbeing of people at different levels of income in Pakistan and to explore how the financial wellbeing is affected by demographic and socioeconomic measures. This study found that different demographic factors may affect the financial wellbeing of Pakistani households in different ways. It is not a postulate that the rich are always happier than poor, but rather they derive their happiness differently. People in urban areas are more likely to have higher financial wellbeing than rural ones. The mediation between household debt and financial wellbeing was also tested and found to be absent. The significant variation in the financial wellbeing was present at provincial level. This study provides a national representative, decade scenario of the debt behaviour of household heads which can be used as a guide to influence household’s demand for debt. This study also reveals the financial wellbeing of Pakistani households and how it can be affected by debt along with other socioeconomic and demographic characteristics.